Incidence of virtual reality in the learning processes of perimeters and areas of regular geometric figures in mathematics - Terán Vaca, Jorge Santiago; Tulcán Angulo, Diana Carolina; Salas Ortiz., Luis Jonás; Nazate Fuel, Ramiro Fabián; Villarreal Chugá, Míriam Elizabeth (SATHIRI, 2025)
The present study investigated the impact of virtual reality on mathematics learning, specifically focusing on the perimeters and areas of regular geometric figures. Employing a quantitative approach, a descriptive quasi-experimental study was conducted with eighth-grade students in basic education. Pre- and post-surveys were utilized to assess students’ motivation before and after the virtual reality intervention. The results revealed a significant increase in students’ motivation after the intervention, supporting the hypothesis that virtual reality positively affects students’ motivation towards mathematics learning. Additionally, positive changes were observed in the perception of complexity, enjoyment, and willingness to continue using virtual reality in mathematics learning. These findings suggest that virtual reality could be considered a tool that offers numerous benefits for increasing student motivation and engagement in mathematics learning. Future research is recommended to be longitudinal, comparative, and focused on the development of new virtual reality applications, aiming to further expand understanding of the use of this technology in mathematics education and enhance students’ learning experiences.